Strategi Bisnis Offline dan Online Untuk Meningkatkan Penjualan Melalui Business Model Canvas : Studi Kasus Hijab Kasiaclothing - Ikhwana, Andri; Febriana, Felinda (Institut Teknologi Garut, 2025)
In the era of growing globalization, business strategy is used to improve the performance of a company so that business strategy can be used as a reference to the plans that occur or steps designed to achieve company goals in the long term and how companies build and improve their competitive position in the industry with the products and services they produce in the market industry. This research uses a descriptive qualitative approach to analyze the problem of declining sales at Kasiaclothing. Using Business Model Canvas as an analytical tool, this research identifies nine interrelated business elements. The resulting strategy includes the integration of offline and online marketing through the optimization of 9 business model canvas elements. This research is expected to contribute to the development of research in the field of business strategy.